2019
DOI: 10.1136/bmj.l1580
|View full text |Cite
|
Sign up to set email alerts
|

Estimates of all cause mortality and cause specific mortality associated with proton pump inhibitors among US veterans: cohort study

Abstract: ObjectiveTo estimate all cause mortality and cause specific mortality among patients taking proton pump inhibitors (PPIs).DesignLongitudinal observational cohort study.SettingUS Department of Veterans Affairs.ParticipantsNew users of PPIs (n=157 625) or H2 blockers (n=56 842).Main outcome measuresAll cause mortality and cause specific mortality associated with taking PPIs (values reported as number of attributable deaths per 1000 patients taking PPIs).ResultsThere were 45.20 excess deaths (95% confidence inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
178
2
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 172 publications
(189 citation statements)
references
References 63 publications
5
178
2
4
Order By: Relevance
“…Recent studies suggested that prolonged PPI exposure was potentially associated with serious adverse effects, including chronic kidney diseases, cardiovascular diseases, or gastrointestinal malignancies, and with a small excess of causespecific mortality [33,34]. PPI therapy should be avoided if not necessary, and deprescribing should be considered whenever possible through regular reevaluation.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies suggested that prolonged PPI exposure was potentially associated with serious adverse effects, including chronic kidney diseases, cardiovascular diseases, or gastrointestinal malignancies, and with a small excess of causespecific mortality [33,34]. PPI therapy should be avoided if not necessary, and deprescribing should be considered whenever possible through regular reevaluation.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the list of potential side-effects related to long-term PPI use is increasing, including among others, chronic kidney disease, osteoporosis and fractures, Clostridium difficile infections, community acquired pneumonia, cardiac diseases, and even increased mortality [8][9][10][11][12][13][14][15][16][17][18][19]. An increasing number of studies have also investigated the risk of cancer with most evidence existing for gastric, colorectal and pancreatic cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Some of these adverse effects are associated with an increased risk of death 9 . Recently, some studies have shown an excessive risk of long‐term all‐cause mortality and cause‐specific mortality among patients using PPIs 9,10 . The potential mechanism may be that the decreased gastric acid secretion and alteration in gut bacterial flora could lead to an increased risk of infection and less absorption of nutrients 11 .…”
mentioning
confidence: 99%